Identification of Macro-Algae Species in Sindangkerta Beach, Tasikmalaya District, an Effort to Explore the Biodiversity of Indigenous Species - Sri Handayani; Cipto Utomo; Nuraidah Nuraidah; Indrastiwi Pramuliati; Achmad Fahreza (Universitas Nasional Jakarta, 2020)
Sindangkerta beach has a total area of ​​90 ha, located in the Sindangkerta village, which is one of the natural tourism areas located on the south coast of West Java, which became one of the mainstays of Tasikmalaya regency. The tourist area is relatively unspoiled and has not maximized its potential. Aside from being a tourist area, Sindangkerta Beach is also a conservation area for sea-turtle breeding. As one of the conservation areas and a tourist spot is certainly a lot of pressure and ecological threats. Handling indigenous species diversity is very important and urgent treated as early as possible to monitor the occurrence of extinction and efforts to develop the existing potential. Data species and morphological descriptions for basic data management and enrichment of biodiversity, especially in Sindangkerta Beach Tasikmalaya. This study was conducted in June 2013 at the Sindangkerta Coastal Waters, District Cipatujah, Tasikmalaya District, West Java Province. The method used Line Transect Square. Sampling was carried out during low tide using square plot. All types of macroalgae found in the square plot were calculated for the number of individuals before the identification process. Macroalgae found in Sindangkerta Beach were 25 species and 17 genera of 3 divisions namely Chlorophyta, Phaeophyta, and Rhodophyta. The highest abundance of macroalgae is Padina australis and Sargassum duplicatum, while the lowest abundance is Halimeda discoidea, Halimeda macroloba, and Laurencia sp. Types of macroalgae that dominate a group Sindangkerta Beach Aquatic included as Phaeophyta (brown algae) categories with the highest dominance type of Padina autralis.